DINAMIKA PERILAKU âNAKALâ ANAK BERAMBUT GIMBAL DI DATARAN TINGGI DIENG - , Puspa Ayu Damayanti, SHI; , Prof. Dr. Endang Ekowarni ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Present qualitative case study is proposed to identify the background of ânaughtyâ behavior of the dreadlock haired children and acknowledges the cause of behavior change post-hair cut. Four dreadlock haired children were took as respondent and 28 informants consist of actor informant as parent, uncle, aunt, grandfather, grandmother and acknowledge-informant as neighbor, teacher and chief of tradition in Dieng plateau. Interview is the only way to collect data of the dreadlock hair since subjects do not have any documentation relate it. Information relate to post-exorcism ritual was collected by interview and observation. Triangulation method and member checking was used for data verification. Research result reveals that the ânaughtyâ behavior of the dreadlock haired children was caused by several factors interdependently which classified into internal and external factors. Internal factor consist of age and physical condition of the dreadlock haired children, whereas the external factor consist of parenting, collective mind power, belief on the dreadlock haired children, perception relate to the dreadlock haired children and demography. The children behavioral changes was caused by two main factors that intertwine namely age and health status as internal factor